Effects Of Flavour Incorporation On Quality And Shelf Life Of Ladoo Prepared From Three Cultivars Of Aonla (Emblica Officinalis Gaertn.) (Applied Biological Research, 2018)
The present study was aimed to develop flavoured ladoo from various  cultivars of aonla and to assess the best suited cultivar and their changes in  its chemical composition and sensory properties during storage. Well  matured aonla (Emblica officinalis Gaertn.) fruits (cv. Banarsi, NA-7 and  Desi) were selected, washed, steamed, de-stoned, pulped and blended with  raw (jaggery)/refined sugar. The blended mass was heated upto 70°Brix and  then ginger and cardamom (8 g kg-1 pulp) flavours were added to it. The  flavoured mass was cooled at room temperature and small ladoo balls  prepared. The ladoos were then stored in pet boxes for 3 months to assess the changes in physicochemical and sensory characteristics. Maximum  mean moisture (21.6%) and browning (0.14 OD at 440 nm) were found in  Desi supplemented with ginger and raw sugar. The highest mean ascorbic acid, iron and phosphorus contents of 128.9, 0.88 and 14.8 mg 100 g-1, respectively, were noticed in flavoured ladoo prepared from cv. NA-7 supplemented with cardamom and refined sugar. An increasing trend in moisture and browning and decreasing trend in ascorbic acid, phosphorus and iron was observed during 3 months storage. On the basis of sensory evaluation (colour, texture, flavour and taste), anola cv. NA-7 ladoo supplemented with cardamom and refined sugar was found the best treatment having good shelf life and can be kept for more than 90 dayswithout any adverse effect on its quality attributes.
Keywords: Aonla; refined sugar; raw sugar; ladoo; ascorbic acid